LA PRATIQUE DE LA CYBERCRIMINALITÉ EN MILIEUX SCOLAIRE ET UNIVERSITAIRE DE CÔTE D’IVOIRE. CAS DES ÉLÈVES ET ÉTUDIANTS DU DISTRICT D’ABIDJAN - N’Guessan, Anon (European Scientific Journal, ESJ, 2014)
The development of the Internet has led to new forms of crime. One of the most prominent felony forms is cybercrime. In Côte d'Ivoire, this phenomenon known as "broutage" has reached such a level that it has become a plague for the youth. In schools and universities, this practice has taken over studies for some young people. Therefore this study is conducted in order to shed light on the manifestations, explanatory factors and consequences of this school and university scourge. The results of this essentially descriptive study revealed that the techniques used are those usually practiced by most cybercriminals: inheritance scams, blackmail, feelings scams, the use of false documents (bank cards, checks ...). As for the explanatory factors, the majority of the surveyed cite at the foreground financial problems and at the background graduate unemployment, lack of parental authority, and the proliferation of cybercafés. It is noted as major impacts, poor performance in class, dropping out, and adoption of behaviors that could lead to committing murder to satisfy their material greed.